New gene functions in megakaryopoiesis and platelet formation - Gieger, Christian; Radhakrishnan, Aparna; Cvejic, Ana; Tang, Weihong; Pistis, Giorgio; Serbanovic-Canic, Jovana; Elling, Ulrich; Goodall, Alison H.; Labrune, Yann; Lopez, Lorna M.; Meacham, Stuart; Sorice, Rossella; et al. (Nature (London), 2011)
Platelets are the second most abundant cell type in blood and are essential for maintaining haemostasis. Their count and volume are tightly controlled within narrow physiological ranges, but there is only limited understanding of the molecular processes controlling both traits. Here we carried out a high-powered meta-analysis of genome-wide association studies (GWAS) in up to 66,867 individuals of European ancestry, followed by extensive biological and functional assessment. We identified 68 genomic loci reliably associated with platelet count and volume mapping to established and putative novel regulators of megakaryopoiesis and platelet formation. These genes show megakaryocyte-specific gene expression patterns and extensive network connectivity. Using gene silencing in Danio rerio and Drosophila melanogaster , we identified 11 of the genes as novel regulators of blood cell formation. Taken together, our findings advance understanding of novel gene functions controlling fate-determining events during megakaryopoiesis and platelet formation, providing a new example of successful translation of GWAS to function. A meta-analysis of genome-wide association studies in more than 66,000 individuals identifies 68 new genomic loci that reliably associate with platelet count and volume, and reveals new gene functions. Gene scan for platelet production Blood platelets are involved in maintaining haemostasis, and platelet count and volume are controlled within tight limits. This meta-analysis of genome-wide association studies in more than 65,000 individuals identifies 53 new genomic loci that reliably associate with platelet count and volume. The loci preferentially map to gene-coding regions, and many of them fall within a single protein–protein interaction network. Functional experiments in zebrafish and fruitflies show that 11 of the newly identified genes encode novel regulators of blood cell formation.